A Review on Future of Information Technology in Agriculture (International Journal of Innovative Research in Computer Science & Technology, 2021)
Agriculture and the industrial sector in  industrialized nations continue to confront issues such as  the need to increase food production and output, as well  as the creation of employment possibilities for poor and  rural people. Economic patterns as well as fast changes  have an impact on the agricultural industry. The results  revealed that there is a significant need for information  technology to be utilized to solve issues, enhance  production, and promote agriculture. However,  information technology (IT's interest in agriculture was  not fully utilized. The adoption of modern information  technology in the rural and agricultural sectors has been  slower than in other economic sectors where it has been  adopted at a faster pace. The purpose of this study is to  look at the function, capability, and involvement of  information technology in this industry, as well as to  show how information technology may be used in various  sectors of agriculture. Their findings were based on  existing literature and economic theory, and they found  that information technology has enormous potential in  assisting farmers and stakeholders in improving  agricultural performance, effectiveness, and profitability.  Players, on the other hand, have additional disadvantages  and challenges when it comes to the use and use of  information technology. There are a variety of ways that  information technology could be used to share data,  including digital kiosks that not only provide essential  resources such as telephone, schooling, health care,  agriculture and irrigation, electronic banking, municipal  services, and so on, as well as specialist networks that  help define marketing options and optimum approaches.  The use of information technology allows for accurate  crop physiology forecasting in agriculture. The study of  leaf protein is an intriguing subject that aids in the  treatment of protein deficit and malnutrition. The present  research focused on the role of information technology on  agricultural productivity.
Keywords: Agriculture; Agribusiness electronic commerce; Farm-level Intelligent Decision Support system; Information Technology